2003
DOI: 10.4049/jimmunol.170.8.4403
|View full text |Cite
|
Sign up to set email alerts
|

HIV-Specific CD8+ T Cell Function in Children with Vertically Acquired HIV-1 Infection Is Critically Influenced by Age and the State of the CD4+ T Cell Compartment

Abstract: The immunology of vertical HIV transmission differs from that of adult infection in that the immune system of the infant is not fully matured, and the factors that influence the functionality of CD8+ T cell responses against HIV in children remain largely undefined. We have investigated CD8+ T cell responses in 65 pediatric subjects with vertically acquired HIV-1 infection. Vigorous, broad, and Ag dose-driven CD8+ T cell responses against HIV Ags were frequently observed in children who were older than 3 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
49
1
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 55 publications
8
49
1
1
Order By: Relevance
“…Preferential targeting of Gag by CD8 + T cells has been linked to better viral control in adults and in older children with HIV infection. 4,9,11,16,17 We did not find a correlation between the magnitude of Gag-specific CD8 + T cell responses and viral load, although the magnitude of a response is not the only indicator of viral control. Studies of HIV-infected adults have indicated that the ability of antigenspecific T cells to perform multiple functions simultaneously (''polyfunctional'') is associated with control of viremia.…”
Section: Nqoko Et Almentioning
confidence: 62%
See 1 more Smart Citation
“…Preferential targeting of Gag by CD8 + T cells has been linked to better viral control in adults and in older children with HIV infection. 4,9,11,16,17 We did not find a correlation between the magnitude of Gag-specific CD8 + T cell responses and viral load, although the magnitude of a response is not the only indicator of viral control. Studies of HIV-infected adults have indicated that the ability of antigenspecific T cells to perform multiple functions simultaneously (''polyfunctional'') is associated with control of viremia.…”
Section: Nqoko Et Almentioning
confidence: 62%
“…11,16 These observations suggest that Gag-specific CD8 + T cell responses may be associated with better viral control and survival. Our findings support this hypothesis, as we showed that infants who survived the first year of life had a significantly higher frequency of Gag-specific CD8…”
Section: Nqoko Et Almentioning
confidence: 87%
“…In other words, less positive selection would have been observed because the transmitted viruses may already have resistance to potential CTL responses that could develop in the child. Another possible explanation is that there are differences in CTL maturity and response between adults and children 6 and the lack of a strong CTL response in children may be due to intrauterine exposure to HIV that results in maturational or developmental abnormalities in CD4 and CD8 cells.…”
mentioning
confidence: 99%
“…7 Generally, HIV-infected children usually need to be older than 3 years of age and have a sufficient number of circulating CD4 T cells to mount a strong and antigen-driven CTL response against HIV. 6 It has been suggested that this weakness of the CTL response against HIV 6 in infants is caused by antigen exhaustion and induction of Th2-like immune responses in early life. 8 Teasing out the mechanisms responsible for any differences in CTL responses between adults and children is complicated, since pediatric HIV infection results in a complex pattern of qualitative and quantitative defects in the immune system 9 and shared HLA-mediated selective pressures on the virus in a vertical transmitting mother-infant pair may undermine future HLA-mediated viral control in the child.…”
mentioning
confidence: 99%
See 1 more Smart Citation